Semi-automated volumetry of MRI serves as a biomarker in neuromuscular patients. - Müller, Madlaine; Dohrn, Maike F.; Romanzetti, Sandro; Gadermayr, Michael; Reetz, Kathrin; Krämer, Nils A.; Kuhl, Christiane; Schulz, Jörg B.; Gess, Burkhard (Muscle & Nerve, 2020)
Background: Muscle MRI is of increasing importance for neuromuscular patients to detect changes in muscle volume, fat-infiltration, and edema. We developed a method for semi-automated segmentation of muscle MRI datasets.Methods: An active contour-evolution algorithm implemented within the ITK-SNAP software was used to segment T1-weighted MRI, and to quantify muscle volumes of neuromuscular patients (n = 65).Results: Semi-automated compared with manual segmentation was shown to be accurate and time-efficient. Muscle volumes and ratios of thigh/lower leg volume were lower in myopathy patients than in controls (P < .0001; P < .05). We found a decrease of lower leg muscle volume in neuropathy patients compared with controls (P < .01), which correlated with clinical parameters. In myopathy patients, muscle volume showed a positive correlation with muscle strength (rleft = 0.79, pleft  < .0001). Muscle volumes were independent of body mass index and age.Conclusions: Our method allows for exact and time-efficient quantification of muscle volumes with possible use as a biomarker in neuromuscular patients.